Influence of deposition temperature on the corrosion resistance of electrodeposited zinc-nickel alloy coatings: Einfluss der Abscheidetemperatur auf die KorrosionsbestÃ¤ndigkeit von galvanisch aufgebrachten Zink-Nickel-Beschichtungen - Beheshti, M. (Wiley-VCH Verlag, 2018)
Zinc-nickel alloy coatings are electrodeposited on carbon steel from chloride bath using a technique of chronopotentiometry at different temperatures. The elemental composition and surface morphology analysis of zinc-nickel coated samples are done using scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy. The coated samples are immersed in 3.5 wt. sodium chloride solution and measurements of corrosion rate are done using linear polarization resistance. Scanning electron microscopy results show that deposition temperature variation has a strong effect which changes the surface morphology and elemental composition of zinc-nickel alloy coatings. The nickel content in the electrodeposited zinc-nickel alloy coatings increases with increasing deposition temperature. Uniformity and compactness of the coatings decrease with an increasing temperature. Cracks intensity increases with increasing deposition temperature which is attributed to internal stress due to factors that might be related to hydrogen evolution reaction. The linear polarization resistance results correlated with the morphology and compositional properties of zinc-nickel alloy coatings deposited at different temperatures, that with an increase deposition temperature, corrosion resistance decreases. Zinc-nickel alloy coatings with high corrosion resistance, compact and uniform morphology with less crack, and nickel content within the range of 12 wt. to 15 wt. are achieved with deposited coating at 25Â Â°C. Â© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim